The Archbishop and the Usurers - Ellis, I. P. (The journal of ecclesiastical history, 1970)
One of the features in common in sixteenth-century episcopal visitations in England, whether Catholic or Reformed, is enquiry after usurers. Bonner's Articles for London in 1554 may be compared in this respect with Grindal's Injunctions for York 17 years later: ‘…Whether in the City of London or diocese of the same name there be any person that is a notorious and common usurer, which lendeth his money for unlawful and excessive gain and lucre, contrary to the manifest words of scripture, to the evil example of other Christian people, to the danger of his own soul, and to the utter undoing and hindrance of many, especially if poor and young beginners, borrowing for their necessity?’ ‘…the churchwardens and sworn men of every parish shall half yearly from time to time present unto the Ordinary the names of all such persons of their parish…as be usurers, that is to say, all those who lend money, corn, ware, or other thing, and receive gain thereof over and above that which they lend’.